UNIVERSITY TEACHERS OF PHYSICAL EDUCATION COURSES: EDUCATION, TECHNOLOGIES AND BODIES ON THE FACEBOOK SCREEN - Missias Moreira, Ramon; Millen Neto, Alvaro Rego; Sousa Mélo, Roberta de (Revista de Educação do Vale do São Francisco, 2019)
The objective of this investigation was to apprehend the corporal representations on facebook of university professors of Physical Education of Brazil and Spain. The Theory of Social Representations and the Studies of Cyberculture have theoretically supported this qualitative research, with a descriptive and analytical approach. They were used as instruments of data production with the 12 teachers: images of the facebook profile, a semi-structured questionnaire and also the dialogues through Messenger that were analyzed through the Content Analysis Technique. The body and its pedagogies teach us new ways of perceiving and constructing educational and pedagogical processes based on the ephemeral light and sweeping brilliance of the metamorphosed bodies. We learn bodily representations of teachers with a view of the spectacle, self-promotion, exhibition contemplation of himself, realizing the cutouts and strategies, through the identification of the fantastic body narratives that populate the modes of being of these subjects and also describe the subjectivities produced by this group of university professors, from their experiences expressed in the images and also in their interactions in this virtual territory. Demonstrating the multiple possibilities of being themselves through these constructed bodily/social narratives